TIPE STOMATA TIGA PULUH DUA JENIS BEGONIA ALAM INDONESIA KOLEKSI KEBUN RAYA CIBODAS - Muhammad Efendi (Research Center for Biology-Indonesian Institute of Sciences, 2019)
Anatomical study on native Begonia in Cibodas Botanical Garden was conducted to determine their stomata types. Stomata 32 native Begonia were prepared by semi-permanent methods. Parameters observed in this study were stomata type, number, and size of stomata. The result showed that all Begonia species have anisocytic stomata and those stomata only found in abaxial leaves. Based on number of stomata, these Begonia can be classified into two groups: single stomata and single-grouped stomata. Generally, Begonia has a single stomata, however, single-grouped stomata is a determinate character of Begonia sect. Reichenheimia and sect. Diploclinium in CBG. The differences of stomata distribution in B. ozotothrix with other members of section Petermannia are needed to be clarified further.